Characterization of camptothecin by analytical methods and determination of anticancer potential against prostate cancer - Sunil T. Galatage; Rahul Trivedi; Durgacharan A. Bhagwat (SpringerOpen, 2021)
Abstract Background Objective of present research work is to develop and validate cost-effective analytical tool for determination of camptothecin (CPT) and determine its anticancer potential against prostate cancer LNCaP cell lines. Structural elucidation has been performed by mass spectrometry, Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, and MTT assay utilized for in vitro cytotoxicity where spectrometric method was used for estimation of camptothecin. Results Mass spectra showed peak at 349.2 which matches to standard molecular weight of camptothecin. FTIR and NMR spectra conformed functional moieties and structure of isolated camptothecin which was nearly equal to values mentioned in standard structure of camptothecin. IC50 values of CPT against LNCaP cell lines was found to be 3.561 μg/ml. Lambda max of CPT was found to be at 225 nm and calibration curve found to be linear over the concentration range from 2 to 70 μg/ml of camptothecin. Developed method was found to be linear, accurate, and precise. LOD and LOQ were found to be 0.0524 μg/ml and 0.1614 μg/ml, respectively. Developed method has % relative standard deviation less than one which is reproducible hence % recovery was found to be 99.80%. Conclusions FTIR, NMR, and mass spectrometry results conforms isolated compound was camptothecin; cytotoxicity study proves it has strong potential in treatment of prostate carcinoma as competent alternative to chemotherapy in the form of herbal medicine and the developed UV method proves to be valid, sensitive, and applicable for rapid, accurate, precise, and economical determination of camptothecin.